2017
DOI: 10.1093/aje/kww147
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Epidemic of Firearm Injury: Increasing Firearm Injury Rates During 2001–2013

Abstract: Investigating firearm injury trends over the past decade, we examined temporal trends overall and according to race/ethnicity and intent in fatal and nonfatal firearm injuries (FFIs and NFIs) in United States during 2001-2013. Counts of FFIs and estimated counts of NFIs were obtained from the Centers for Disease Control and Prevention's Web-based Injury Statistics Query and Reporting System. Poisson regression was used to analyze overall and subgroup temporal trends and to estimate annual change per 100,000 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 13 publications
4
41
1
Order By: Relevance
“…One report analyzed data from the Centers for Disease Control and Prevention combining annual counts of fatal and non-fatal firearm injury from 2002 to 2011 and concluded that firearm lethality was declining evidenced by stagnant rates for firearm homicide with rising rates of non-fatal firearm assault. 15 However, after correcting for facilities reporting to the sample, a separate analysis concluded that firearm lethality from assault has been constant from 2003 to 2012. 9 There is active debate on the merits and limitations of both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…One report analyzed data from the Centers for Disease Control and Prevention combining annual counts of fatal and non-fatal firearm injury from 2002 to 2011 and concluded that firearm lethality was declining evidenced by stagnant rates for firearm homicide with rising rates of non-fatal firearm assault. 15 However, after correcting for facilities reporting to the sample, a separate analysis concluded that firearm lethality from assault has been constant from 2003 to 2012. 9 There is active debate on the merits and limitations of both approaches.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of injuries far exceeds fatalities, state data regarding firearm injuries is neither comprehensive nor accessible. 4,7 Since most firearm injuries are nonfatal, many associations are unmeasurable when only fatalities are considered. A comprehensive database of all firearm injuries including fatalities would greatly facilitate future firearm injury research and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…1,4 These injuries burden both the medical community and the American healthcare system with massive costs. In a recent report, Spitzer et al estimated the cost of initial hospitalizations alone for patients injured by firearms in America to be $734.6 million per year—a figure that multiplies to several billions when long-term medical care and employment loss are included.…”
mentioning
confidence: 99%
“…Data are collected by trained, onsite hospital coders who enter all elements of an encounter except cause of injury, which is classified by quality assurance coders at the Consumer Product Safety Commission headquarters in Bethesda, MD . This dataset has been used as the basis of many previous publications, including recent reports on traumatic brain injuries occurring at playgrounds, and trends in nonfatal firearm injuries …”
Section: Methodsmentioning
confidence: 99%